2021
DOI: 10.1111/nmo.14242
|View full text |Cite
|
Sign up to set email alerts
|

Effect of slow, deep breathing on visceral pain perception and its underlying psychophysiological mechanisms

Abstract: Background Studies using somatic pain models have shown the hypoalgesic effects of slow, deep breathing. We evaluated the effect of slow, deep breathing on visceral pain and explored putative mediating mechanisms including autonomic and emotional responses. Methods Fifty‐seven healthy volunteers (36 females, mean age = 22.0 years) performed controlled, deep breathing at a slow frequency (6 breaths per minute), controlled breathing at a normal frequency (14 breaths per minute; active control), and uncontrolled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 80 publications
(159 reference statements)
0
7
0
4
Order By: Relevance
“…Gholamrezaei and collaborators estimated that SPB had no effect on pain through vagal activation, but rather suggested that other mechanisms, such as attentional modulation (distraction) may underlie this effect (Gholamrezaei et al, 2021b(Gholamrezaei et al, , 2021a.…”
Section: Pain Sensation Regulationmentioning
confidence: 99%
“…Gholamrezaei and collaborators estimated that SPB had no effect on pain through vagal activation, but rather suggested that other mechanisms, such as attentional modulation (distraction) may underlie this effect (Gholamrezaei et al, 2021b(Gholamrezaei et al, , 2021a.…”
Section: Pain Sensation Regulationmentioning
confidence: 99%
“…A recent study by Gholamrezaei et al (2022) also observed that SDB could decrease visceral pain intensity. Botha et al (2015) reported that the development of acidinduced esophageal hypersensitivity could be prevented by deep breathing.…”
Section: Discussionmentioning
confidence: 79%
“…Practice logs were recorded to ensure that the experimental group met the practice requirements. Participants in both groups were instructed to maintain 10.3389/fnins.2022.1034547 their regular diet and exercise regimens (Lee et al, 2021;Gholamrezaei et al, 2022).…”
Section: Measurements Slow Deep Breathing Interventionmentioning
confidence: 99%
“…47 Both deep diaphragmatic breathing techniques and mindfulness practices might enhance pain coping strategies, decrease pain catastrophizing, and improve overall psychological well-being. 48,49 In addition, to the best of our knowledge, no previous study assessed the effects of a tele-yoga intervention in patients with chronic NSLBP. In this context, tele-approach and digital innovation are emerging concepts in healthcare.…”
Section: Discussionmentioning
confidence: 99%